Production optimization and tribological characteristics of cottonseed oil methyl ester. (1st February 2019) - Jamshaid, M.; Masjuki, H.H.; Kalam, M.A.; Zulkifli, N.W.M.; Arslan, A.; Alwi, Azham; Khuong, L.S.; Alabdulkarem, Abdullah; Syahir, A.Z.
Abstract: This paper presented experimental results to evaluate the optimization of production parameters through response surface methodology. These parameters significantly affected the yield of cottonseed oil methyl ester (COME). The input variables for the production of methyl ester from cottonseed oil were methanol/oil molar ratio, concentration of catalyst, temperature, and stirring speed. The response or output variable was the yield of methyl ester. The fatty acid methyl ester composition of COME (biodiesel) was obtained using a gas chromatography (GC) analyzer. BS EN 14103:2011 was the standard used to analyze the fatty acid methyl ester. The derived mathematical model was statistically accurate to predict the optimum value of COME. The optimized values to obtain a 98.3% yield of methyl ester were as follows: methanol/oil molar ratio of 6:1, catalyst concentration of 0.97% (w/w), temperature of 63.8 °C, and speed of 797 rpm. The physicochemical properties of COME were measured in accordance with ASTM D6751. The friction and wear properties of COME and its blends with petroleum diesel were tested using a four-ball wear testing machine. The tribological characteristics of COME as a new biofuel were assessed. COME displayed good lubricity with a low coefficient of friction and wear scar diameter. The coefficient of friction of pure COME (COME100) was lower than that of pure petroleum diesel (DL100) and COME blends with petrol diesel (COME10, COME20, and COME50). The average coefficient of friction of COME 100 was lower than that of DL100, COME10, COME20, and COME50 by 28.06%, 19.49%, 7.49%, and 3.65%, respectively. The wear scar diameter of COME100 for the tested ball was lower than that of DL100, COME10, COME20, and COME50 by 47.6%, 33.3%, 32.1%, and 21.42%, respectively. The worn surfaces of the tested balls were examined by scanning electron microscopy, and the results were presented in this paper. Highlights: The response surface methodology was utilized to optimize the production process parameters. The tribological characteristics of cottonseed oil methyl ester (COME) as a new biofuel were assessed. Friction and wear were reduced with increased concentration of COME in the testing fuel. The average coefficient of friction was reduced with increased concentration of COME in the testing fuel. The wear scar diameter of worn surfaces was enhanced with the reduction of COME concentration in the testing fuel.